The Seeds of Doubt: Finding Seeds in Intriguing Places - Grillo, Federica; Campora, Michela; Cornara, Laura; Cascini, Alberta; Pigozzi, Simona; Migliora, Paola; Sarocchi, Francesca; Mastracci, Luca (Frontiers in Medicine, 2021)
Introduction: Seeds may be found in gastrointestinal samples, and their multifaceted appearance may be challenging. The aim is to report a rough incidence of pathology samples which show seeds, specify the most frequent sample types and show an iconography of the most commonly identified seeds. Materials and methods: Between 2017 and 2020, all gastrointestinal pathology cases in which seeds/seed parts were found, were collected and seed type described by referencing a seed image library. Results: Fifty cases with complete seeds/seed parts were collected: 16 colonic resections for colorectal cancer and diverticulosis, 13 appendiceal resections for appendicitis, 1 gastric resection. Fifteen cases were found in polypectomy specimens and 5 cases in colorectal endoscopic biopsies. Most frequent seed types were tomato, kiwi, blueberry and blackberry seeds. Conclusion: Seeds may be found in up to 4% of specimens; their recognition may be useful to exclude parasitic infections as well as in forensic sciences.